Bacteriophage as carrier for multiple DNA vaccine in poultry - Al-Tayyar, O. B.; Siang, T. W.; Omar, Abdul Rahman; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Bacteriophage-mediated immunization is a novel vaccine technology for DNA-vaccine delivery which has many advantages over traditional vaccines. The risk of reversion is absent, it can induce both humoral and cellular immunity, large-scale production is cheaper and its transportation is easier as there are no particular storage requirements. After viral RNA extraction, the specific genes were amplified using reverse-transcriptase polymerase chain reaction (RT-PCR). The amplified PCR products were inserted into bacteriophage lambda vector and successful recombinant were confirmed by white-blue screening, colony-PCR and sequencing. The aim of this study is to produce a multiple bacteriophage-mediated DNA-vaccine for poultry production.